The global EPTO database: Worldwide occurrences of aquatic insects - Grigoropoulou, Afroditi; Hamid, Suhaila Ab; Acosta, Raúl; Akindele, Emmanuel Olusegun; Al-Shami, Salman A.; Altermatt, Florian; Amatulli, Giuseppe; Angeler, David G.; Arimoro, Francis O.; Aroviita, Jukka; Astorga-Roine, Anna; Bastos, Rafael Costa; et al. (Wiley, 2023)
Motivation: Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database, which includes worldwide geo-referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained: A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub-catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain: The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain: Sampling years span from 1951 to 2021. Ninety-nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub-datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement: Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format: The entire tab-separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/. Fifty individual datasets are also available at https://fred.igb-berlin.de, while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.
Keywords: aquatic insects; biodiversity; Ephemeroptera; freshwater ecosystems; global dataset; observation records; Odonata; Plecoptera; species distributions; Trichoptera